Being alert: bridging theory and practice in public sector entrepreneurship. Issue 7 (3rd October 2019) - Arnold, Aaron
Abstract : Purpose: Studies on entrepreneurship in public agencies suggest that managing for innovation may increase organizational performance. These studies, however, do not take into consideration the processes of opportunity identification. Therefore, the purpose of this paper is to, first, situate the concept of opportunity identification within the broader research on public sector entrepreneurship, and second, to explore the relationship between managerial empowerment practices and employee alertness to new opportunities. Design/methodology/approach: This paper uses aggregated data from the Federal Employee Viewpoint Survey – an annual survey of the US Federal employees – to examine the relationship between managerial empowerment practices and employee alertness. The analysis employs a fixed-effects regression to model each panel of the US Federal agencies, from 2011 to 2017. Findings: The results indicate that managerial empowerment practices have a clear correlation to employee alertness and are substantively different from empowerment practice's relationship to "innovation" – an outcome of entrepreneurship. These findings suggest that scholarship should include opportunity identification as a moderating variable in future studies on public sector entrepreneurship. Research limitations/implications: The empirical analysis should be viewed as a novel approach to alertness in order to demonstrate the need to include opportunity identification processes in studies on managing for public sector entrepreneurship. Consequently, the results are not generalizable to all public agencies. Originality/value: This paper highlights processes of entrepreneurial opportunity identification concerning management practices in the public sector, which scholarship has traditionally ignored.